TINDAK PIDANA ILLEGAL LOGGING KETERKAITAN APARAT DALAM PENEGAKAN KEBIJAKAN HUKUM PIDANA: (Studi Kasus di Kabupaten Blora, Provinsi Jawa Tenggah) - Wirasaputri, Nina Mirantie (PROGRESIF: Jurnal Hukum, 2019)
Criminal sanctions cumulatively , impact / consequences of criminal acts in the field of Forestry is detrimental to the country's financial , economic and social sanctions it should not only a criminal sanctions to perpetrators with penalties as severe as a loss , but also must be considered a country with sanctions " action planning orderly " In addition to fulfilling a sense of justice should be the formulation of a criminal sanction criminal acts in the forestry sector carried out by civil servants or government officials , especially the officials who have authority in the field of forestry , which could increase the intensity of Forestry organized crime and formulated specifically that of course the formulation of sanctions the criminal is not the same as that carried criminal sanctions against people / person.